SPATIAL MOMENT APPROACH IN IDENTIFYING MOVING RAINSTORMS DURING THE JAKARTA FLOOD EVENT - Haniyah Firstrizanda, Faza
Several studies related to the influence of moving rainstorms show that moving rainstorms plays a significant role in influencing discharge. In the extreme Jakarta flood events in 2013 and 2020, radar reflectivity data showed cloud propagation which indicated the movement of rainfall at each event time. The identification of moving rainstorms utilizes a spatial moment approach that is considered capable of characterizing spatial rainfall organization features in the statistical parameters of concentration and spatial rainfall distribution as a function of distance to the outlet measured along the catchment flow path. Analysis of the time-to-time variation of rainfall-weighted flow distance to the outlet allows calculation of catchment-scale rainfall velocity. The obtained values of rainfall concentration and distribution in both event years were consistent when compared to the hovmoller plot showing rainfall propagation, rain velocity calculations were performed hourly to detect the velocity during the event, the results showed fluctuating values but detected the speed of rainfall propagation upstream marked by positive rain velocities at 14.00-15.00 WIB on January 15, 2013 and 04.00-06.00 WIB for January 1, 2020. In general, the use of spatial moment statistics isolates the spatial variability features of rainfall for the time of occurrence.